2011
DOI: 10.4067/s0716-97602011000200002
|View full text |Cite
|
Sign up to set email alerts
|

Gamete interactions in teleost fish: the egg envelope. Basic studies and perspectives as environmental biomonitor

Abstract: The current knowledge about teleost fi sh egg envelope is summarized. The paper analyzes the organization and deposition process of the protein composition and genes involved in the synthesis of teleost fi sh egg envelopes and their role in gamete interaction during fertilization. Pelagic and demersal species that our research group is working with are especially considered. The vertebrate ZP family of proteins, the evolution and relationship among the different genes and their expression are taken into accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 50 publications
(53 reference statements)
3
14
0
Order By: Relevance
“…In M. robustus , it was found that the zona pellucida appears during the PG stage, as reported by other authors (Berois et al, ; Berois et al, ; Uribe et al, . In this study various morphological changes of peripheral ooplasm of the follicle were documented concomitantly with the development of the zona pellucida suggesting a relationship between these morphological changes and the development of the zona pellucida before the vitellogenesis.…”
Section: Discussionsupporting
confidence: 82%
“…In M. robustus , it was found that the zona pellucida appears during the PG stage, as reported by other authors (Berois et al, ; Berois et al, ; Uribe et al, . In this study various morphological changes of peripheral ooplasm of the follicle were documented concomitantly with the development of the zona pellucida suggesting a relationship between these morphological changes and the development of the zona pellucida before the vitellogenesis.…”
Section: Discussionsupporting
confidence: 82%
“…The development of the zona pellucida in M. robustus began during the deposition of oil droplets during primary growth, it is similar to those mentioned in several species by Wourms (); Dummont & Brummet (); Berois, Arezo, Chalar, Brauer and Barros (); Berois, Arezo and Papa (); Uribe et al (, ). In M. robustus, the striated or radial morphology of the zona pellucida was appreciated during SGe, but the beginning of formation of parallel bands was observed during SGfg, before the maturation of oocytes, as reported by Berois et al (, ), and as described by Domínguez‐Castanedo et al (). This feature of the zona pellucida suggests that the oocytes observed in M. robustus no longer received outer material, vitellogenesis was over and oocytes were close to the Maturation Stage, beginning the morphological transformation of the zona pellucida to the embryonic chorion (Dummont & Brummet, ), a structure for ulterior embryonic protection.…”
Section: Discussionsupporting
confidence: 81%
“…Brind, Alani, Matias, Markofsky and Rizer (1982), considered that oil droplets are essential nutrients which go through long periods; suggesting that in annual killifishes, the oil droplets can serve as an extra reservoir for Diapause III embryos for the potential delay in the filling the pond by a shortage of rainfall in an unusual year; suggesting that it is an important struc- (2011); Uribe et al (2012Uribe et al ( , 2016. In M. robustus, the striated or radial morphology of the zona pellucida was appreciated during SGe, but the beginning of formation of parallel bands was observed during SGfg, before the maturation of oocytes, as reported by Berois et al (2007Berois et al ( , 2011…”
Section: Primary Growth Stagementioning
confidence: 81%
“…One important-but understudied-source of MEs in numerous taxa, from simple, sexually reproducing multi-cellular organisms to amphibians and mammals, are egg coats, which are maternally derived extracellular structures that surround the organism during early life stages. These structures can have major impacts on fitness, as they both mediate the beginning of life (due to their fundamental role in fertilization) and protect the embryo from a range of environmental hazards (e.g., Wong and Wessel 2006;Hedrick 2008;Menkhorst and Selwood 2008;Berois et al 2011). They can even facilitate speciation (e.g., Palumbi 2009).…”
Section: Introductionmentioning
confidence: 98%